2005
DOI: 10.1016/j.otohns.2004.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Can mobile phone emissions affect auditory functions of cochlea or brain stem?

Abstract: Together with the results of a previous article concerned with the vestibular part of the inner ear, we can state that there are no adverse effects of mobile phone emissions on the ear function, at least on a short-term range. Of course, any long-term effects cannot be excluded by our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 18 publications
1
21
2
Order By: Relevance
“…Other studies were excluded from the review because the authors did not meet criteria (a), (b) and (c) [Ozturan et al, 2002;Bak et al, 2003;Oysu et al, 2005;Pau et al, 2005], whereas Arai et al [2003] did not satisfy criteria (a) and (c). The study of Sievert et al [2005] did not meet criteria (a) and (b), while criteria (b) and (c) were not satisfied in experiments carried out by Eulitz et al [1998] and Esen and Esen [2006]. Moreover, the study by Hietanen et al [2000] did not satisfy criteria (c) and (d).…”
Section: Literature Search and Selectionmentioning
confidence: 95%
“…Other studies were excluded from the review because the authors did not meet criteria (a), (b) and (c) [Ozturan et al, 2002;Bak et al, 2003;Oysu et al, 2005;Pau et al, 2005], whereas Arai et al [2003] did not satisfy criteria (a) and (c). The study of Sievert et al [2005] did not meet criteria (a) and (b), while criteria (b) and (c) were not satisfied in experiments carried out by Eulitz et al [1998] and Esen and Esen [2006]. Moreover, the study by Hietanen et al [2000] did not satisfy criteria (c) and (d).…”
Section: Literature Search and Selectionmentioning
confidence: 95%
“…As of yet, there is no clear evidence of mobile phone radiation effects on auditory brainstem and cochlear responses [Arai et al, 2003;Aran et al, 2004;Sievert et al, 2005]. To our knowledge, no records of electrophysiological changes in the auditory system during the exposure to EMR of mobile phones have been performed.…”
Section: Introductionmentioning
confidence: 97%
“…7,[18][19][20][21]23,24 Various papers have suggested that exposure to mobile phone microwaves has no influence on the activity of cochlear outer hair cells or of cochlear nerve electrical conduction, both in vivo and in vitro. 8,11,15,25,26 Another point is that all of the studies on humans were carried out on normal-hearing volunteers. It is not know whether the cochlea of patients with inner ear conditions would be more sensitive to electromagnetic radiation.…”
Section: Discussionmentioning
confidence: 99%
“…BERA was done before and immediately after a 15-minute telephone call. The authors found no significant variation in waves I, II and V, or in the interpeak intervals I-III, III-V and I-V. Sievert et al (2005) 26 tested the influence of continuous or pulsed microwaves on the BERA of 12 healthy volunteers. The test was done before, during and after using a mobile phone.…”
Section: ) Short-term Effectsmentioning
confidence: 99%